Microbiological and mycotoxin risk assessment in ruminant feeding in Sulaimani governorate - Hamasalim, Hozan Jalil; Khan, Karwan Muhamad Hama; Sadq, Sarwar Muhamad (Sulaimani Journal for Pure and Applied Sciences, 2016)
Background: Feed contamination and poisoning by microbial and fungal genera pose obvious health threat to animals. Method: Vesa, ZAB, MIK, Deern, Zano and Zizar types of ruminant feed used in Sulaimani Governorate were analyzed for their bacterial and fungal quality. Identification of fungal isolates with determination of aflatoxin, ochratoxin and T-2 toxin for all trademarks and local feed and the prime target of this research would be background foreshadow for some danger of ruminant feedstuff in Sulaimani governorate and taking these aspects in consideration to assess microbiological quality and mycotoxins in ruminant feed. Result: The genera of bacteria and fungi isolated and their occurrence were Salmonella sp., total plate count and total fungal count. Based on standard method identification of fungal species in brands ruminant feed and local ruminant feed, the all commonly isolated genera were Aspergillus spp., Penicillium spp and Fusarium spp. Finally, detected concentration of each aflatoxin, ochratoxin and T-2 toxin in brands ruminant feed and local ruminant feed. Most types of ruminant feed under study were lower than the maximal standard limits of aflatoxin while all types of brands ruminant feed and local ruminant feed under study were lower than the maximal tolerance limits of ochratoxin and T-2 toxin.
Keywords: Ruminant Feed; Microbiological Quality; Identification of Fungal and Mycotoxin